2018
DOI: 10.4081/aiua.2018.3.203
|View full text |Cite
|
Sign up to set email alerts
|

Hibiscus extract, vegetable proteases and Commiphora myrrha are useful to prevent symptomatic UTI episode in patients affected by recurrent uncomplicated urinary tract infections

Abstract: Objective: To evaluate the efficacy of a combination of Hibiscus extract, vegetable proteases and Commiphora myrrha extract in the prophylaxis of symptomatic episode in women affected by recurrent urinary tract infections (rUTIs). Materials and methods: In this phase II clinical trial, all patients with history and diagnosis of rUTI were enrolled. All patients underwent the following treatment schedule: 1 tablet in the morning and 1 tablet in the evening for 7 days and, then, 1 tablet in the evening for 10 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
(23 reference statements)
0
4
0
1
Order By: Relevance
“…In particular, the use of phytotherapy and nutraceuticals might represent a feasible and effective, alternative approach to curtail the use of antibiotics and the rate of symptomatic recurrences [3,13,19,20]. Recently, Cai et al published a paper about the efficacy of a combination of Hibiscus extract, vegetable proteases and Commiphora myrrha extract, for preventing symptomatic UTI episodes and improving patients' QoL [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, the use of phytotherapy and nutraceuticals might represent a feasible and effective, alternative approach to curtail the use of antibiotics and the rate of symptomatic recurrences [3,13,19,20]. Recently, Cai et al published a paper about the efficacy of a combination of Hibiscus extract, vegetable proteases and Commiphora myrrha extract, for preventing symptomatic UTI episodes and improving patients' QoL [12].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we excluded all patients with active infection by sexually transmitted pathogens. Immediately before enrolment a clinical and microbiological evaluation was performed by administering QoL questionnaires and performing a preliminary midstream urine culture, in line with Cai et al [3,12]. All screened women were informed about the nature of the study and about the fact that the suggested product is already present in Italy.…”
Section: Study Design and Treatment Schedulementioning
confidence: 99%
See 2 more Smart Citations
“…З огляду на низький рівень використання менопаузальної гормональної терапії в Україні (1-2%), зростання резистентності до антибіотиків, підвищення обізнаності про шкідливу дію антибактеріальних засобів на мікробіом піхви та кишечника, збільшення частоти рецидивів ІСШ, перед науковцями постає проблема пошуку альтернативних методів лікування ІСШ у жінок у клімактеричному періоді [9,15,21,26].…”
Section: вступunclassified